2013
DOI: 10.1080/14786419.2013.827192
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antimicrobial activities of Snakin-Z, a new cationic peptide derived fromZizyphus jujubafruits

Abstract: Snakin-Z is a novel antimicrobial peptide (AMP) that is identified from the fruit of Zizyphus jujuba. This peptide is composed of 31 amino acids which is determined with the sequence of CARLNCVPKGTSGNTETCPCYASLHSCRKYG and molecular weight of 3318.82 Da. Snakin-Z is not identical to any AMP in the peptide database. According to this study, Snakin-Z potentially has antimicrobial property against bacteria and fungi. Minimal inhibitory concentration (MIC) value of this peptide is suitable for antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…and A. niger (IC 50 = 1 to 20 µm). Other snakins, such as a 64-residue homolog of StSN2 identified in French bean or snakin Z isolated from Jujuba fruits, are active against A. niger (Daneshmand, Zare-Zardini, & Ebrahimi, 2013). Another 66-residue snakin-2 (Sn2) found in tomato shows a broad-spectrum activity, including against S. cerevisiae (MIC = 4.25 µM).…”
Section: Snakinsmentioning
confidence: 99%
“…and A. niger (IC 50 = 1 to 20 µm). Other snakins, such as a 64-residue homolog of StSN2 identified in French bean or snakin Z isolated from Jujuba fruits, are active against A. niger (Daneshmand, Zare-Zardini, & Ebrahimi, 2013). Another 66-residue snakin-2 (Sn2) found in tomato shows a broad-spectrum activity, including against S. cerevisiae (MIC = 4.25 µM).…”
Section: Snakinsmentioning
confidence: 99%
“…Snakin-Z peptide composed of 31 amino acid with molecular weight 3318.82Da from the fruit of Zizyphus jujube showed antimicrobial activity against bacteria and fungi whereas it was found to be ineffective against human red blood cells 93 . This indicated that Snakin -Z could be a suitable candidate of antimicrobial peptides for therapeutic applications.…”
Section: Six Main Families Of Pampsmentioning
confidence: 99%
“…Additionally to this classification, several classes of plant AMPs can also be divided by properties, such as covalent bonding patterns, hydrophobicity, net charge, or molecular targets (Wang, 2015). Among several different plant AMP classes, in fruits it is possible to detect (I) defensins (Meyer et al, 1996; Guzmán-Rodríguez et al, 2013; Seo et al, 2014), (II) lipid transfer proteins (LTPs) (Zottich et al, 2011), (III) glycine rich protein (Pelegrini et al, 2008), (IV) 2S albumin (Pelegrini et al, 2006; Ribeiro et al, 2011), (V) snakin (Daneshmand et al, 2013), (VI) napin (Da Silva Dantas et al, 2014), and (VII) and other fruit AMPs (Table 1). …”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%
“…Snakin-Z AMP, isolated from Z. jujuba , is 31 amino acid residues in length and has better activity againt fungi than bacteria (Terras et al, 1992; Thevissen et al, 1999; Selitrennikoff, 2001; Tran et al, 2002; Manners, 2009). Among bacteria, its action is stronger against Gram-negative than Gram-positive bacteria (Daneshmand et al, 2013). …”
Section: Fruit Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation